Resolutions of Conflicts among Radical Beliefs through the Wisdom of Cultural Values - Khaerul Umam (UIN Sunan Gunung Djati Bandung, 2022)
This study seeks to identify a form of cultural reconciliation applied by the community to the radical belief clash between Dayak Indramayu mysticism and the Muslim community in Indramayu Regency, West Java, Indonesia. This study employed a strategy for resolving cultural conflicts by collecting data via observation and in-depth interviews with both parties. This investigation yielded multiple findings. First, the fight between Dayak Indramayu and Muslims in the Indramayu Regency is a religious dispute. The crisis began when the Indonesian Ulema Council (MUI) labelled Dayak Indramayu group as heretical. Following the labelling, Dayak Indramayu responded by criticizing Islamic religious leaders who engage in numerous unethical behaviours. Second, although this dispute affected religious leaders on both sides, it had no effect on the religious followers at the grassroots level. Thirdly, religious conflicts involving religious leaders and beliefs can naturally lessen due to the community-owned and religious leader-guided cultural framework. The author identifies this as a cultural resolution to religious problems. This study contributes to two aspects. First, as a model for resolving interfaith problems that can be replicated abroad through the application of cultural values' wisdom. Second, this idea of resolution contributes to the corpus of religious studies on the management of religious conflicts founded in radical views.